2014
DOI: 10.1108/jeim-06-2012-0032
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing critical success factors of total quality management by using fuzzy cognitive mapping

Abstract: Purpose – Total quality management (TQM) is a process and philosophy to achieve customer satisfaction in long term by improving the products, processes and services effectively and efficiently. TQM implementation is turning into a complex practice due to the increasing number of effective factors and key elements labelled as critical success factors (CSFs). The purpose of this paper is to analyse the relations between CSFs of TQM and to provide decision makers has a clear picture of relations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…we provide information using advanced technologies]. • • Leadership-Some respondents to our survey indicated that the leadership of their organizations exhibits a strong commitment to quality, which further indicates that they recognize the importance of the top management commitment to quality (Kutlu & Kadaifci, 2014) [. .…”
Section: • • Knowledge and Information Sharing-our Resultsmentioning
confidence: 99%
“…we provide information using advanced technologies]. • • Leadership-Some respondents to our survey indicated that the leadership of their organizations exhibits a strong commitment to quality, which further indicates that they recognize the importance of the top management commitment to quality (Kutlu & Kadaifci, 2014) [. .…”
Section: • • Knowledge and Information Sharing-our Resultsmentioning
confidence: 99%
“…Due to dealing with a network model, fuzzy cognitive maps (FCMs) that allow dynamic modeling of a system in consideration of a complex network structure can be chosen but the main purpose of the FCM is to determine the causal relationships between factors and tries to find the effects of factors on others in the long run (Kutlu and Kadaifci, 2014;Yaman and Polat, 2009). On the other hand, System Dynamics that captures the causal relationships and interdependence of the factors (Tesfamariam and Lindberg, 2005) and The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method which is used for presenting the complex structure of causal relationships between factors (Jassbi et al, 2011) can also be used.…”
Section: Why Anp?mentioning
confidence: 99%
“…An FCM was generated for the study by combining the fuzzy set theory and neural networks from the basic cognitive mapping method (Kosko, 1986). An FCM map can be used to represent the complex and dynamic behaviour of the elements within a system (Can Kutlu & Kadaifci, 2014). Because of its ability to model complex and ambiguous systems with fuzziness and uncertainty, researchers have used this tool Berger et al (2001), Gasbarro, Sadguna and Zumwalt (2002), Khalid (2006), Cooper (2009), Kumar et al, (2012) across various applications (Katiyar et al, 2018;Uzochukwu et al, 2016).…”
Section: Fuzzy Cognitive Maps and Fuzzy Micmac Analysismentioning
confidence: 99%
“…Applications of FCM can be seen in total quality management (TQM) and vendor selections as well. Can Kutlu and Kadaifci (2014) have used FCM to analyse the critical success factors of TQM in order to help the decision makers to better understand their interrelations. Hanafizadeh and Zadeh (2015) have used FCM to combine mental maps in order to design a solution for vendor selection.…”
Section: Fuzzy Cognitive Maps and Fuzzy Micmac Analysismentioning
confidence: 99%
See 1 more Smart Citation